2019
DOI: 10.1590/0037-8682-0447-2018
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis in the Middle Paranapanema river region, state of São Paulo, Brazil: Does it matter today for public health?

Abstract: Introduction: The Middle Paranapanema watershed is known for the transmission of schistosomiasis, and there have been autochthonous cases since 1952. This study aimed to describe this disease in space and time and evaluate its current importance as a public health problem. Methods: Thematic maps showing the risk areas for transmission of schistosomiasis, using scan statistics, and flow maps were created in the period 1978-2016. Incidence was calculated, and the existence of spatial dependence between autochtho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
3
0
5
Order By: Relevance
“…29 Socio-economically precarious communities where low schooling levels together with environmental problems prevail, are characterized by these additional factors which result in these problems continuing, within a context in which reinfection is facilitated. [1][2][3][4][5][6][7]9,10,12,14,16,18,[23][24][25][26][27][28][29] The reduction in the percentage of positivity for other helminthiases may be associated with treatment with low toxicity medication (albendazole, mebendazole), which has taken place for decades in Brazil and has been reinforced by SANAR. 7,25 Data from the national survey on the prevalence of Manson's schistosomiasis and geo-helminthiases showed that periodic use of these low cost and easy to administer forms of medication is responsible for the reduction in approximately 80% of cases of other helminthiases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Socio-economically precarious communities where low schooling levels together with environmental problems prevail, are characterized by these additional factors which result in these problems continuing, within a context in which reinfection is facilitated. [1][2][3][4][5][6][7]9,10,12,14,16,18,[23][24][25][26][27][28][29] The reduction in the percentage of positivity for other helminthiases may be associated with treatment with low toxicity medication (albendazole, mebendazole), which has taken place for decades in Brazil and has been reinforced by SANAR. 7,25 Data from the national survey on the prevalence of Manson's schistosomiasis and geo-helminthiases showed that periodic use of these low cost and easy to administer forms of medication is responsible for the reduction in approximately 80% of cases of other helminthiases.…”
Section: Discussionmentioning
confidence: 99%
“…1 Moreover, the severe clinical forms in which schistosomiasis manifests itself contribute to its magnitude and transcendency. 5,6 Pernambuco is one of the Northeastern states with high schistosomiasis prevalence. 2 As a classically chronic and rural disease, associated with poverty and occurring above all in the Zona da Mata (an area where the soil is fertile, rivers are perennial and not subject to periodic droughts), schistosomiasis took on new facets to its epidemiological profile when it began to occur in the acute form, in outbreaks located along the state's coast.…”
Section: Introductionmentioning
confidence: 99%
“…A (Barbosa, 1995;Lenzi, 2008 A perpetuação do ciclo ocorrerá com a migração dos vermes adultos ao intestino, onde terá início o acasalamento de machos e fêmeas, caracterizando o início do processo de oviposição na luz intestinal eliminando os ovos juntamente com as fezes do indivíduo infectado (Watson et al, 1960;Brasil, 2008;Lenzi, 2008;Espírito-Santo et al, 2012Palasio et al, 2019).…”
Section: Introductionunclassified
“…áreas de transmissão autóctone da EM no estado de São Paulo estão localizadas no Vale do Ribeira, Vale do Paraíba, Litoral Norte, Baixada Santista, Grande Campinas e alguns municípios da Região Metropolitana de São Paulo, incluindo a capital(Brasil, 2008) onde a espécie B. tenagophila é predominanteLenzi, 2008). A única exceção está relacionada com os casos procedentes dos criadouros naturais de B. glabrata, restritos a coleções de água no trecho médio do Rio Paranapanema (Figura 2) onde a espécie coloniza inúmeras coleções hídricas(Palasio et al, 2019). que diz respeito à Ourinhos, a ocupação urbana gerou impactos ambientais duradouros sobre os sistemas hídricos da paisagem, sendo estes todos pertencentes às microbacias afluentes dos Rios Pardo e Paranapanema(Figura 3).…”
unclassified
See 1 more Smart Citation